Hroniskas subdurālas hematomas klīnika, diagnostika, ārstēšana - Rogačova, Nataļja (Latvijas Universitāte, 2015)
Tēmas aktualitāte: Hroniska subdurāla hematoma ir viena no biežākām neiroķirurģiskām patoloģijam gan Latvijā, gan visā pasaulē. Ar katru gadu subdurālās hematomas biežums pieaug. Tāpēc pētījumā mērķis noteikt hroniskas subdurālas hematomas etioloģiju, izvērtēt un izvēlēties optimālu terapijas taktiku. Pētījums atspoguļos patreizējo epidemioloģisko situāciju pacientiem ar hronisko subdurālo hematomu, kā arī dos ieskatu par hroniskas subdurālas hematomas etioloģiju, ļaus salīdzināt un noteikt medikamentozās, un ķirurģiskās ārstēšanas efektivitāti. Materiāli un metodes: Pētījumā tika iekļauti cilvēki, kas stacionēti Paula Stradiņa klinīskā universitātes slimnīcā pēdējo 5 gadu laikā. Dati ievākti no medicīnisko dokumentu arhīva. Pētījums noritēja PSKUS medicīniskajā arhīvā. Secinājumi: Pētījumā tika konstatēts, ka vīriešiem HSDH attīstības risks ir augstāks nekā sievietēm. Biežākais HSDH attīstības cēlonis ir galvas trauma, antikoagulantu un antiagregantu lietošana. HSDH biežāk attīstās pacientiem, kuriem ir alkohola atkarība un arteriālā hipertensija. HSDH biežāk sastopama gados vecākiem cilvēkiem. Vidējais HSDH pacientu vecums sastāda 63 gadus. Visiem pacientiem, kuriem radioloģiski pieradīta HSDH un ir neiroloģiskie simptomi, indicēta ķirurģiska hematomas evakuācija. Pacientiem, kuriem HSDH norit asimptomātiski, radioloģiski nav viduslīnijas nobīdes, kā arī nav smadzeņu kompresijas klīnīkas, visslabāk pielietot konservatīvo ārtēšanu un veikt rūpīgo novērošanu. Lielākā daļa no visiem pacientiem, pēc saņemtās ārstēšanas izveseļojas pilnībā. Diagnosticējot slimību, nepieciešams veikt DT/MR un koagulācijas profilus

Relevance of the topic: Chronic subdural haematoma is one of the most common neurosurgical disorders both in Latvia and worldwide. Every year subdural haematoma incidents increase. Wherefore the study aims to determine the aetiology of chronic subdural haematoma, evaluate and choose the treatment strategy. The study will provide insight into the epidemiological situation in patients with chronic subdural haematoma, and its results will give insight into the aetiology of chronic subdural haematoma, enable comparison and determination of medicinal and surgical treatment effectiveness. Materials and methods: The study involves people who have been hospitalised in Pauls Stradins Clinical University Hospital over the last 5 years. Data collected from the medical archives. The study held in the PSCUH medical archives. A structured anonymous questionnaire will be developed for the purpose of the study having been previously approved by the Ethics Commission. The study group includes 100 people aged 18 to 89 years. The data collected using the data collection questionnaire from the patients' medical records: Socio-demographic characteristics, chronic subdural haematoma aetiology, chronic subdural haematoma localisation and size, types of diagnosis, received treatment, types of surgical treatment and medical treatment. The obtained data collected, processed and statistically analysed using MS Excel and SPSS 19.0 (Statistical Package for the Social Sciences) software. The data processed with descriptive statistics methods. Statistical significance observed if the P value is <0.05. Conclusions: The study showed that the risk for development of CSDH is higher for men than for women. The most common cause for CSDH development is a head trauma, using anticoagulants and antiplatelet agents. CSDH often develops in patients who are dependent on alcohol and suffer from arterial hypertension. CSDH is more common in older people. The average age of the patients with CSDH is 63 years. To all patients with radiologically evidenced CSDH and neurological symptoms was assigned surgical evacuation of haematoma. The patients, in whom CSDH is asymptomatic, no midline shift radiologically, and no cord compression clinics, best to be assigned to conservative treatment and given to a careful observation. Most of all the patients after received treatment recovered fully. Diagnosing the disease, it is necessary to carry out CT/MRI and coagulation profiles.
Chronic subdural hematoma clinic, diagnostics, treatment
Keywords: Medicīna; hroniska subdurāla hematoma; ķirurgija; ārstēšana; diagnostika; klīnika